2008
DOI: 10.1007/s11748-007-0208-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis of flomoxef in children undergoing cardiopulmonary bypass and modified ultrafiltration

Abstract: The pharmacokinetics of flomoxef in children undergoing CPB and MUF were well fitted to a modified two-compartment model. Using the kinetic data from this study, the individualization of dosage regimens for prophylactic use of flomoxef might be possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…These differences were most profound during DHCA, suggesting that plasma levels might not be predictive of the skeletal muscle concentrations in all patients, highlighting one of the limitations of previous studies of prophylactic antibiotics in children undergoing CPB using the plasma level as a surrogate for the tissue concentration. [20][21][22][23] Furthermore, despite the routine use of cefazolin for SSI prophylaxis in congenital cardiac surgery, only 1 published study has measured cefazolin in plasma, and that study was limited because it did not report the unbound cefazolin levels or tissue concentrations. 21 The most common side effect related to the microdialysis catheters was minor bleeding (defined as 1-3 drops of blood) at the insertion sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences were most profound during DHCA, suggesting that plasma levels might not be predictive of the skeletal muscle concentrations in all patients, highlighting one of the limitations of previous studies of prophylactic antibiotics in children undergoing CPB using the plasma level as a surrogate for the tissue concentration. [20][21][22][23] Furthermore, despite the routine use of cefazolin for SSI prophylaxis in congenital cardiac surgery, only 1 published study has measured cefazolin in plasma, and that study was limited because it did not report the unbound cefazolin levels or tissue concentrations. 21 The most common side effect related to the microdialysis catheters was minor bleeding (defined as 1-3 drops of blood) at the insertion sites.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 PK studies of prophylactic antibiotics during CPB in children have used both total and unbound plasma concentrations as a surrogate for the tissue drug concentrations. [20][21][22][23] However, the plasma concentrations might not accurately reflect the antimicrobial exposures in the tissue where an infection occurs. Tissue concentrations might represent the true target for SSI prevention and could be important to better determine the recommendations for prophylactic antibiotic dosing.…”
Section: Methodsmentioning
confidence: 99%
“…Masuda et al found that almost one-fourth of the given dose of Flomoxef (a second generation cephalosporin antibiotic with a broad spectrum) was removed by MUF in children undergoing cardiac surgery. 30…”
Section: Drugsmentioning
confidence: 99%
“…However, the PK parameters of a drug can change with disease, with concomitant drug therapy, and even within the same individual according to the clinical situation, such as being connected to a heart-lung machine 13) or undergoing PD. Among the deductively produced PK modeling approaches, the physiological concept of an integrated PK (physiological PK) model is successful in complying with the diversity of prediction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that such deductive modifications have implications for individualized prophylactic use of antibiotics in children undergoing cardiopulmonary bypass surgery and modified ultrafiltration. 13) Propranolol hydrochloride (PPL), a sympatholytic non-selective ¢-blocker, 14) is administered to patients to treat hypertension. Cefazolin sodium (CEZ) is clinically effective against infections caused by staphylococci and streptococci of Gram-positive bacteria and is generally used to treat moderately severe bacterial infections involving the lungs, bones, joints, stomach, blood, heart valves, and urinary tract.…”
Section: Introductionmentioning
confidence: 99%